2013
DOI: 10.1016/j.paid.2013.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among higher-order strengths factors, subjective well-being, and general self-efficacy – The case of Israeli adolescents

Abstract: We investigated relationships among five higher-order strengths factors, subjective well-being, and general self-efficacy in participants that live under challenging conditions. Therefore, a sample of 396 Israeli adolescents (aged 13-18 years) completed the Values in Action Inventory of Strengths for Youth, the Satisfaction With Life Scale, the Affect Balance Scale, and the General Self-Efficacy Scale. An orthogonally rotated principal component analysis of the 24 character strengths yielded five strengths fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
72
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 17 publications
13
72
0
8
Order By: Relevance
“…Past studies showed that SWB had a meaningful relationship of shyness and self-efficacy, shyness and self-efficacy plays a mediator role between this in a sample of Chinese college students (Wang, 2013 [42] ; Li, 2014 [50] ). It should be mentioned that self-efficacy has been found to mediate the relationship between the characteristic or other sociological factors and SWB (Cohen, 2012 [19] ; Strobel et al, 2011 [20] ; Weber et al, 2013 [21] ). Furthermore, there are studies proved the mediating effect of self-efficacy between subjective and other variables such as internet, attachment (Huang, 2006 [51] ; Hampton, 2004 [52] ).…”
Section: Social Support and Subjective Well-beingmentioning
confidence: 99%
“…Past studies showed that SWB had a meaningful relationship of shyness and self-efficacy, shyness and self-efficacy plays a mediator role between this in a sample of Chinese college students (Wang, 2013 [42] ; Li, 2014 [50] ). It should be mentioned that self-efficacy has been found to mediate the relationship between the characteristic or other sociological factors and SWB (Cohen, 2012 [19] ; Strobel et al, 2011 [20] ; Weber et al, 2013 [21] ). Furthermore, there are studies proved the mediating effect of self-efficacy between subjective and other variables such as internet, attachment (Huang, 2006 [51] ; Hampton, 2004 [52] ).…”
Section: Social Support and Subjective Well-beingmentioning
confidence: 99%
“…Prior research found specific character strengths to be positively related to different aspects of subjective well-being, like global life satisfaction or happiness (e.g., Park and Peterson 2006;Ruch et al 2014;Toner et al 2012), and to general, domain-free positive affect, and negatively related to general, domain-free negative affect (e.g., zest, hope, love, gratitude) (e.g., Van Eeden et al 2008;Weber et al 2013), and to a list of discrete positive emotions (Güsewell and Ruch 2012). The present study has been designed to examine character strengths' relation to school-related affect by hypothesizing students' character strengths to be positively related to school-related positive affect, and negatively to schoolrelated negative affect.…”
Section: Character Strengths and Schoolingmentioning
confidence: 99%
“…Self-efficacy beliefs also affect the self-evaluation = autonomous evaluation standards students use to judge the outcomes of their self-monitoring (in our research study as AAA). Self-efficacy beliefs also motivate students' use of learning strategies (Weber et al, 2013). …”
mentioning
confidence: 99%